COVID-19 and Immigration: Reflections From the Penn State Law Center for Immigrants' Rights Clinic - Box, Kaitlyn; Wadhia, Shoba Sivaprasad (Frontiers in Human Dynamics, 2020)
Since the 2016 Presidential Election, the Center for Immigrants’ Rights Clinic (CIRC) at Penn State Law in University Park has been at the forefront of responding to rapidly changing immigration policies that include the “travel ban,” efforts to end a policy called “DACA”, policies to curb asylum at the southern border, and efforts to more easily exclude international students and scholars. Some of the tools CIRC has used to respond to these changes include easy to understand “fact sheets”, in person and virtual “town halls,” and legal support for individuals fighting deportation or seeking refuge. This essay will use CIRC as a case study to demonstrate how one set of student advocates used the same tools developed over three years of responding to ever-evolving immigration policies to respond to changes surrounding COVID-19. Specifically, we describe CIRC’s responses to changes at international borders, stalemates in immigration detention, expansions to asylum restrictions, and the status of DACA at the Supreme Court. This article explains how the same responses that have long been used to address the current administration's immigration changes can also be used to respond to immigration policy changes resulting from the COVID-19 pandemic. This essay discusses how CIRC responded to each significant immigration policy change arising out of COVID-19, as well as explains how CIRC moved from an in-person to remote platform in spring 2020 alongside many law clinics across the country, shares reflections from those students, and offers lessons that can be drawn for legal education moving forward.